HUBUNGAN KUALITAS PELAYANAN DAN KEPUASAN DENGAN LOYALITAS PASIEN RAWAT JALAN DI RSIA TIARA FATRIN PALEMBANG - Arief Fardiansyah; Dwi Helynarti Syurandhari; Restu Handayani (STIKes Al-Insyirah Pekanbaru, 2022)
Various efforts made by hospitals to provide the best service to patients are expected to increase patient satisfaction and strengthen patient loyalty to return to the same hospital if they experience health problems. This study aims to determine the relationship between service quality and satisfaction with the loyalty of outpatients at RSIA Tiara Fatrin Palembang. The research design is correlational analytic with a cross-sectional approach. The population was 96 respondents, sampling as many as 52 respondents using purposive sampling techniques. The measuring instrument used is a questionnaire, and the results are processed through the stages of editing, coding, scoring, tabulating, and testing using the Spearman Rho test. The results of the study found that of 52 respondents, almost half stated that the quality of service was good and loyal patients 22 respondents (42.3%), almost half stated respondents expressed satisfaction and loyalty, namely 25 respondents (48.1%). There is a relationship between service quality with patient loyalty with a probability value / Asym.sig of 0.001 which is < α (0.05 ) and there is a relationship between patient satisfaction with patient loyalty with probability values / Asym.sig of 0.000 and < α (0.05). There is a relationship between service quality and patient loyalty at RSIA Tiara Fatrin Palembang in 2022 and there is a relationship between patient satisfaction and patient loyalty at RSIA Tiara Fatrin Palembang in 2022. Excellent service in hospitals must be carried out by paying attention to internal and external factors, with the hope of the emergence of satisfaction, trust, and loyalty of patients to visit again. Keywords: Quality; Service; Satisfaction; Loyalty; Patients